Yes Today, No Tomorrow: Exploration of Deal Cancellations in Televised Pitch Competitions - Boerner, Livia; Frick, Bernd; Fritz , Thomas (American Journal of Management, 2025)
Early-stage entrepreneurs exert significant efforts to secure deals with angel investors, but many are canceled during the due diligence process. Drawing upon interpersonal persuasion theory and information asymmetries in the pitch context, we investigate deal cancellations as instances of biased communication and strategic misrepresentation. We analyze a novel dataset comprising N = 1,334 pitches from the British Dragons’ Den and the German Die Höhle der Löwen format. Our examination delves into differences related to gender and team size of the involved parties, format, and level of financial risk. We find a bias against female investors, higher cancellation rates for more costly deals, and a country effect.